2009
DOI: 10.2106/jbjs.h.01814
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Iliac Bone-Grafting for Osteonecrosis with Segmental Collapse of the Femoral Head

Abstract: Vascularized iliac bone-grafting with use of the technique described in this study is not indicated for the treatment of osteonecrotic femoral heads with segmental collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 15 publications
3
72
0
Order By: Relevance
“…7,22 In the present study, histological examination of collapsed femoral heads revealed end-stage osteonecrosis with segmental collapse, as is observed in human osteonecrosis. 23 Destructive repair leading to femoral head deterioration has also been found in quadruped models, but without resulting in femoral head collapse. 8,9 Loading onto the osteonecrotic zone also contributes to femoral head collapse, 24 and the differences in the hipjoint biomechanics between bipedal and quadrupedal animals might be the crucial factor resulting, or not resulting, in subsequent joint collapse.…”
Section: Discussionmentioning
confidence: 99%
“…7,22 In the present study, histological examination of collapsed femoral heads revealed end-stage osteonecrosis with segmental collapse, as is observed in human osteonecrosis. 23 Destructive repair leading to femoral head deterioration has also been found in quadruped models, but without resulting in femoral head collapse. 8,9 Loading onto the osteonecrotic zone also contributes to femoral head collapse, 24 and the differences in the hipjoint biomechanics between bipedal and quadrupedal animals might be the crucial factor resulting, or not resulting, in subsequent joint collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Their overall succes rate of entire group was 87.5% according to ARCO staging system. [24] However, contrast of the others, Chen et al, [19] reported that the use of vascularized iliac bone grafting may not be as promising as originally suggested. They carried out a retrospective review of 33 hips treated with pedicled iliac bone block over the five years, resulting 76% required THA at mean of 74 months.…”
Section: Discussionmentioning
confidence: 96%
“…Several head preserving procedures such as core decompresion, osteotomies and non-vascularized or vascularized bone grafting have been used to avert the need for total hip replacement. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The vascularized fibular grafting is associated with better clinical and radiographic results than non-vascularized fibular grafting in precollapse hips. [9][10][11][12] The rationale of vascular pedicled fibula grafting procedure is based on the following points: decompression of the femoral head diminishes intraosseous pressure like compartment syndrome and improves the interrupted circulation which contributes the disease progression.…”
mentioning
confidence: 99%
“…However, joint-sparing therapeutic techniques are associated with variable outcomes depending on the staging and complexity of the procedures. [2,[4][5][6]8,[11][12][13] Core decompression for Steinberg stage I disease was successful as a definitive procedure in more than 80% of patients. Steinberg stage II and III osteonecrosis were treated with decompression without requiring further surgical reconstructive intervention in 63% and 29%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some of these procedures are technically demanding or have donor side morbidity. [12][13][14] To improve the initial mechanical support to the femoral head and to prevent further collapse, a large amount of allografts or synthetic bone substitutes are needed [15,16] for impaction after cord decompression. Calcium sulfate (CaSO 4 ) and calcium phosphate (CaPO 4 ) are the commonly used bone substitutes in fracture and benign bone lesions.…”
mentioning
confidence: 99%